METHODS OF MODERN LABORATORY DIAGNOSTICS OF INFECTIOUS DISEASES - Ibragimova Nadiya Sabirovna; Isakulova Muhabbat Mardanovna; Daminov Feruz Asadullaevich; Shahobiddinova Xosiyat Xushvaxtovna (TADQIQOTLAR.UZ, 2024)
Annotation. At the earliest stages of the disease, it is very important to identify pathology, which will significantly reduce the need to use highly invasive diagnostic methods, allow timely identification of treatment options, and prediction of possible outcomes and the likelihood of relapse of the disease. Therefore, one of the main goals of modern laboratory diagnosis is to identify biomarkers of diseases.